Evaluations of the Antimicrobial Activities and Chemical Compositions of Body Fat from the Amphibians Leptodactylus macrosternum Miranda-Ribeiro (1926) and Leptodactylus vastus Adolf Lutz (1930) in Northeastern Brazil. (23rd April 2013) - Cabral, Mario Eduardo Santos; Dias, Diógenes de Queiroz; Sales, Débora Lima; Oliveira, Olga Paiva; Teles, Diego Alves; Filho, João Antonio de Araujo; Sousa, José Guilherme Gonçalves de; Coutinho, Henrique Douglas Melo; Costa, José Galberto Martins da; Kerntopf, Marta Regina; Alves, Rômulo Romeu da Nóbrega; Almeida, Waltécio de Oliveira
Abstract : Leptodactylus macrosternum and L. vastus (family: Leptodactylidae) are commonly encountered in the "Caatinga" biome in northern Brazil. The body fat of L. vastus is used as a zootherapeutic for treating a number of human maladies. The aim of this work was to determine the chemical composition of the body fats of L. macrosternum and L. vastus and to evaluate their antimicrobial activities as well as the ecological implications of their use in traditional folk medicine. Oils were extracted from body fat located in the ventral region of L. macrosternum (OLM) and L. vastus (OLV) using hexane as a solvent. The fatty acids were identified by GC-MS. The antimicrobial activities of the oils, either alone or in combination with antibiotics and antifungal drugs, were tested on standard strains of microorganisms as well as on multiresistant strains of Escherichia coli and Staphylococcus . OLM contained 40% saturated and 60% unsaturated fatty acids, while OLV contained 58.33% saturated and 41.67% unsaturated fatty acids. Our results indicated that both OLM and OLV demonstrated relevant antimicrobial activities (with MIC 256 μ g/mL for both) against Pseudomonas aeruginosa and Candida krusei . However, no antimicrobial effects were observed when these oils were combined with antibiotics or antifungal drugs.